Incentive and spill-over effects of supplementary sickness compensation - Patrik Hesselius; Malin Persson (Institute for Labour Market Policy Evaluation (IFAU), 2007)
In 1998 the Swedish national sickness insurance policy changed to allow additional compensation from e.g. collective agreements after the 90th day of absence without a reduction of the public sickness benefit. We estimate the effects of this policy change on the duration of sickness absence for employees in the municipal sector. After the change in policy, this group received 10 percentage points additional compensation during day 91 to 360 in a sick leave. The results indicate that durations of at least 91 days increased by 4.7 days on average. As a consequence, the cost for the national sickness insurance increased by 3.0 percent. For the supplementary insurance to cover its total cost, insurance premiums should be increased by 22 percent.
Keywords: H51; H55; I38; J22; 330; Social insurance; sickness absence; collective agreements; Gesetzliche Krankenversicherung; Krankheit; Dauer; Fehlzeit; Schweden